2012
DOI: 10.1111/j.1365-2966.2012.21098.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing the time variability of five Fe low broad absorption-line quasars

Abstract: We study the time variability of five Fe low‐ionization broad absorption line (FeLoBAL) QSOs using repeated spectroscopic observations with the 2‐m telescope at IUCAA Girawali Observatory (IGO) spanning an interval of up to 10 years. We report a dramatic variation in the Al iii and Fe iii fine‐structure lines in the spectra of SDSS J221511.93−004549.9 (zem∼ 1.478). However, there is no such strong variability shown by the C iv absorption. This source is known to be unusual with (i) the continuum emission domin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…In the sample of unusual BAL quasars of Hall et al (2002), the detection of the UV34 triplet is much more common than UV48, which would be expected if ionization of Fe  is the dominant mode of populating the UV34 lower level. However, if the UV48 absorption is stronger than that of UV34, as in SDSS 2215-0045 (Hall et al 2002;Vivek et al 2012), the above-mentioned Fe  excited-level population scenario, which works well for GRB 080310, does not provide a viable explanation. Table 3 of Paper I), for H , C , Si , Cr , Fe  and Fe  (from top to bottom panels).…”
Section: Discussionmentioning
confidence: 99%
“…In the sample of unusual BAL quasars of Hall et al (2002), the detection of the UV34 triplet is much more common than UV48, which would be expected if ionization of Fe  is the dominant mode of populating the UV34 lower level. However, if the UV48 absorption is stronger than that of UV34, as in SDSS 2215-0045 (Hall et al 2002;Vivek et al 2012), the above-mentioned Fe  excited-level population scenario, which works well for GRB 080310, does not provide a viable explanation. Table 3 of Paper I), for H , C , Si , Cr , Fe  and Fe  (from top to bottom panels).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have revealed that the fractional variation of BAL troughs in lower ionization transitions (such as Si iv) is generally stronger than that in C iv (e.g., Capellupo et al 2012;Vivek et al 2012;Filiz Ak et al 2013). A recent study by Filiz Ak et al (2013) presented a detailed investigation of the variability of C iv and Si iv BALs on multi-year timescales in a large quasar sample assessing variation characteristics and the lifetimes of BAL troughs.…”
Section: Introductionmentioning
confidence: 99%
“…Vivek et al (2012) saw variable time-scales down to ∼1.2 yr in one out of the five FeLoBAL quasars in their sample, and attributed the changes to Fe iii and Al iii fine-structure lines. Hall et al (2011) detected absorption line variability over 0.6-5 yr in the FeLoBAL quasar J1408+3054, observing dramatic changes in Mg ii and disappearance of Fe ii lines at the same velocity; using a different outflow model than the one adopted in our analysis, Hall et al (2011) constrained the absorber distance to be between 1.7 and 14 pc from the SMBH, in approximate accord with our results.…”
Section: Comparisons To Previous Workmentioning
confidence: 98%
“…Hall et al (2011) observed dramatic changes in Mg ii and a disappearance of the Fe ii lines at the same velocity in FBQS J1408+3054, and constrained the outflow to be between 1.7 and 14 pc from the SMBH based upon a model with clouds moving across the LOS. Vivek et al (2012) probed the time variability of five FeLoBAL sources, reporting changes from Fe iii and Al iii fine structure absorption lines in one of those objects and concluded that those ions likely originated in the ISM based upon ionization considerations and a model from Rogerson et al (2011).…”
Section: Introductionmentioning
confidence: 99%